Age Dynamics of Professional Self-determination of Children with Special Needs - Кots Myxajlo; Polishchuk О. (Psychological Prospects Journal, 2015)
This article gives theoretical analysis and empirical investigation of professional self-deternination age dynamics of children with disabilities (7–11 forms) with impaired mental and physical development. Data are given about the meaning and importance of professional self-determination process for pupils with disabilities studying in a specialized educational and rehabilitation center. It should be emphasized that a significant number of young people with impaired mental and physical development face serious problems associated with the choice of profession, profile further education, further employment. The purpose of scientific research was to reveal and explore patterns and characteristics of professional self-determination of children with special needs at different age periods. It is shown that the originality of the intellectual and physical development of children with intellectual disabilities complicates a choice of profession as opposed to the choice of secondary school pupils. Participants of the empirical research were pupils of Lutsk Education and Rehabilitation Center. Conclusions are made that the most distinct aptitude for certain type of occupations is monitored in the 9th and 11th forms. The least distinct aptitude is peculiar to pupils of the 7th and 10th forms. The age of the seventh form pupils is characterized by a wide range of interests and cognitive activity. Pupils of 10th form are characterized by uncertainty and fear of adulthood and the understanding that they have time to think about their future. It is examined that the development parameters of school-leavers’ interests (the 9th and 11th forms) indicate the specificity of this age that is choosing a further education and a professional field. Clear differences in motivational complexes of students at different development stages are distinguished.